(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the contribution of Imam al-Bukhari to the holy religion of Islam, the importance of education, the universal significance of the spiritual heritage of the great hadith scholar and leader of the faithful in the science of hadith, Imam al-Bukhari, in the upbringing of the younger generation with the noble ideas expressed in his works, and the educational significance of the scholar’s works in the development of spiritual and moral qualities and the formation of positive qualities in the education of young people.